Evaluating the knowledge and attitudes of trainee clinical officers (COs) and the behavior of qualified COs in identifying and managing common mental disorders in Malawi - Matoga, Ellliot (Department of Psychiatry and Mental Health, 2024)
Background: A high proportion of individuals with serious mental illness remain without treatment partly due to serious shortages of healthcare workers. The result is a large treatment gap for mental disorders in Malawi and globally. To expand mental health coverage in low-income countries (LIC) we require the implementation of strategies that have shown to be feasible and effective such as: integration of mental health into primary healthcare, and expansion of human capacity through task shifting and training of non-specialist health workers. Adequate training is required to improve Clinical Officers' (CO) professional knowledge, attitudes and skills about mental illness so that they are better able to assess, identify and manage mental illness. COs' training consists of a two week psychiatry and mental health theory module, followed by four weeks of practical attachment at a psychiatric hospital. Currently, we do not know whether the curriculum for COs in its present form is effective in increasing knowledge and addressing attitudes of COs towards mental illness. Aim: The aim of this study was to evaluate the impact of training on knowledge and attitudes of trainee COs and explore the qualified COs' experience of the Malawian clinical context and their application of learned skills in identifying and treating mental health disorders in primary healthcare patients. The specific objectives for the study were as follows: 1) To measure changes in mental health knowledge and attitudes of trainee COs before and after receiving psychiatry and mental health training; 2) To explore the application of taught skills by qualified COs in identifying and treating people with mental disorders in Primary Health Care (PHC) clinics. Methods: This study consists of a quantitative and a qualitative component. In the quantitative phase, sixty-two trainee COs at the Malawi College of Health Sciences (MCHS) in Malawi completed pre- and post-training questionnaires assessing knowledge, attitudes and skills. The questionnaire comprised the following sections: 1) Socio-demographic questions, 2) The Mental Illness: Clinician's Attitudes Scale (MICA) Version 4 and 3) WHO mental health gap action plan (mhGAP) questionnaire for assessing knowledge. In the qualitative phase, nine COs working in PHC facilities in the Southern Region in Malawi were interviewed using semi-structured interviews to explore the application of skills in identifying and treating mental disorders. Results: There was a significant difference in attitude scores before and after the training (t (61) = 3.77, p < 0.001). The overall mean score of the MICA-4 was 45.03 (SD: 6.86) before training and 41.18 (SD: 8.31) after training suggesting decreased levels of stigmatizing attitudes. Knowledge mean scores increased from 11.16 (SD: 3.01) before training to 12.69 (SD: 2.66). There was a statistically significant difference in knowledge mean scores indicating an improvement in knowledge before and after the training (t (61) = - 4.39, p < 0.001). The qualitative interviews provided insight into the difficulties COs experience in the application of skills learnt in pre-service training. The key service level barriers to the provision of mental health service in Malawi were identified as lack of knowledge, lack of in-service training, drug shortages and inadequate pre-service training programs. Conclusion: The two-week psychiatry training for COs improved knowledge and attitudes but may not be sufficient in ensuring adequate mental health services at PHC level. Qualified COs working in the healthcare system identified factors such aslack of knowledge, inadequate pre-service training programs, lack of in-service training and drug shortages as key service level barriers to the provision of effective mental health services in Malawi. The training of COs could be strengthened by improving the assessment and management of mental health conditions